Providing, Performing and Protecting: The Importance of Work Identities in Negotiating Conflicting Work–Family Ideals as a Single Mother. (3rd March 2021) - Radcliffe, Laura; Cassell, Catherine; Malik, Fatima
Abstract: The aims of this paper are twofold. First, we aim to expand understanding of work–family experiences beyond the prevalent emphasis on traditional couple‐headed families within organization and management literatures by focusing on the experiences of employed single mothers. Second, we aim to gain insight into how work and family meanings may be negotiated in the context of heightened conflicting ideals and demands. Drawing on rich qualitative data from in‐depth interviews and diaries, our findings make three important contributions to the existing work–family literature. First, we show that conflicting work and family ideals are not only exacerbated for single mothers, but viable narrative strategies with which to negotiate this conflict are also restricted. Second, we highlight how narratives constructed around the meaning of work are key to single mothers' negotiation of conflicting work and family ideals and identify three work narratives drawn upon by single mothers focused on providing, performing and protecting. Finally, we demonstrate how shifts between single mothers' work narratives are particularly influenced by progression opportunities and a supportive work environment. We conclude by making suggestions for future work–family research.